Effects of gamma irradiation on GaN high-electron-mobility transistors characterized by the voltage-transient method. (30th July 2021) - Pan, Shijie; Feng, Shiwei; Li, Xuan; Zheng, Xiang; Lu, Xiaozhuang; Hu, Chaoxu; He, Xin; Bai, Kun; Zhou, Lixing; Zhang, Yamin
Abstract: The effects of gamma irradiation on the electrical and trapping properties of AlGaN/GaN high-electron-mobility transistors (HEMTs) are investigated in detail. During the irradiation, the gate–source leakage current of the HEMT is monitored online when applying a reverse gate voltage. The variations of electrical properties of the device, including an increase in drain–source current, the negative threshold voltage shift, and a decrease of leakage current, are observed. In particular, three traps in the device are identified using the voltage-transient method and the variations of these traps after irradiation are also investigated. The results show that the absolute amplitudes of the three traps in the device decrease after irradiation, which indicates a reduction in the density of the traps. Furthermore, it is proposed that the time constants and energy levels of the three traps decrease after irradiation. The observed changes in the trapping behaviors are ascribed to the structural ordering of the defects, which is consistent with the improvement in the electrical characteristics of the device.